A small-sized spectrometric detection block of the scintillator-photodiode system for determination of radionuclide localization sites - Nekrasov, V.V.; Belogub, V.V.; Borodenko, Yu.A.; Gektin, A.V.; Grinyov, B.V.; Selegenev, E.M. (Functional Materials, 2005)
A new small-sized spectrometric gamma-radiation detection block of scintillator-photodiode system has been developed. The block is of θ10x60 mm² size and consists of a Csl(TI)-Si PD detector, charge-sensitive amplifier, shaper and an output matching channel. The sensitivity at E = 60 keV is 0.2 pulse·s⁻¹/μR•h⁻¹ Разработан новый малогабаритный спектрометрический блок детектирования у-излучения системы сцинтиллятор-фотодиод. Блок имеет размеры 010x60 мм2 и состоит из детектора Csl(TI)-Si ФД зарядочувствительного усилителя, формирователя и выходного согласующего каскада. Чувствительность блока при Е = 60 кэВ составляет 0,2 имп.-сек⁻¹/мкР-час⁻¹. Розроблено новий малогабаритний спектрометричний блок детектування у-випромі-нювання системи сцинтилятор-фотодіод. Блок має розміри θ10x60 мм² і складається з детектора Csl(TI)-Si ФД, зарядочутливого підсилювача, формувача та вихідного узгоджуючого каскаду. Чутливість блока при Е = 60 кеВ складає 0,2 імп.-сек⁻¹/мкР-год⁻¹.